Detection of Norovirus and Rotavirus in Children under Five Years During Winter 2012-2013 in Mosul Province - Mohamed, Nadira Salman; Hameed, Mohammed Fadhel; Al-Rubai, Haider Khadum (Al-Nahrain Journal of Science, 2018)
The identifying the viral agents such as norovirus genogroup I (NVGI), norovirus genogroup II (NVGII) and rotavirus (RV) is critical to the development of effective preventive measures. This study aimed to determine the prevalence of common enteric viruses in children <5 years old presented with diarrhea in Mosul Governorate. Due to the lack of recent reports on surveillance of ro¬tavirus and norovirus infection in, One hundred fecal samples were collected between December 2012 to March 2013 from children <5 years of age who presented with acute gastroenteritis in the Al-Salam hospital and Al-Madena clinical laboratory in Mosul .All samples were tested for rotavirus using latex agglutination test, and norovirus using (RT-qPCR) for NVGI and NVGII. Enteric viruses were detected in 42 out of the 100 (42%) children who presented with acute diarrhea. In that 42 samples positive for enteric viruses, at least one viral agent was found. NVGII was the most frequent virus identified in 24cases (57.14%), followed by rotavirus in 14 cases (33.33%), and NVGI in 4 cases (9.52%). The result demonstrated a high prevalence infection with the both viruses in age group under 1years with high incidence of 22 Bottle-Feed 22 cases (52.37%).Norovirus and Rotavirus co-infection was occurred in 9 cases presented 21.24% of all cases.